Pengaruh Persepsi Harga, Kualitas Produk, Promosi Dan Citra Merek Terhadap Minat Beli - Zsazsa Baziska Ulitama; Desy Prastyani (Jurnal Publikasi Ilmu Manajemen, 2023)
The more the times and the more sophisticated technology, the more widespread the application of human lifestyle in everyday life. This study aims to determine the effect of price, product quality and promotion on buying interest mediated by brand image on the Levi's brand. This research method uses a type of causal research using (SEM-PLS). The results of hypothesis analysis show that perceived price, product quality, and promotion have a significant positive effect on brand image, and perceived price and product quality also have a significant positive effect on purchase intention. However, there is no significant support for the relationship between promotion and purchase intention, and brand image does not act as a mediating variable between perception and purchase intention. In conclusion, marketing strategies need to focus on building brand image through perceived price, product quality, and promotion, while evaluating alternative ways to directly link brand image with purchase intention. The managerial implication is the importance of focusing on marketing strategies that build brand image through perceived price, product quality, and promotion, and the need to explore ways to directly link brand image with consumer purchase intention.